2012
DOI: 10.1242/dev.069963
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional co-regulation of neuronal migration and laminar identity in the neocortex

Abstract: The cerebral neocortex is segregated into six horizontal layers, each containing unique populations of molecularly and functionally distinct excitatory projection (pyramidal) neurons and inhibitory interneurons. Development of the neocortex requires the orchestrated execution of a series of crucial processes, including the migration of young neurons into appropriate positions within the nascent neocortex, and the acquisition of layer-specific neuronal identities and axonal projections. Here, we discuss emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
349
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(372 citation statements)
references
References 137 publications
(235 reference statements)
10
349
0
4
Order By: Relevance
“…S2F and Table S2). It is generally believed that the migration of excitatory neurons in the neocortex stops at P7 (21). We found that deletion of CX26 did not affect the laminar distribution of tdTomato + CX26-cKO neurons compared with tdTomato + CX26-WT neurons in the neocortex at P6 (SI Appendix, Fig.…”
Section: Conditional Deletion Of Cx26 In Excitatory Neurons At Earlymentioning
confidence: 64%
“…S2F and Table S2). It is generally believed that the migration of excitatory neurons in the neocortex stops at P7 (21). We found that deletion of CX26 did not affect the laminar distribution of tdTomato + CX26-cKO neurons compared with tdTomato + CX26-WT neurons in the neocortex at P6 (SI Appendix, Fig.…”
Section: Conditional Deletion Of Cx26 In Excitatory Neurons At Earlymentioning
confidence: 64%
“…The genome-wide significant top SNP from our GWAS (rs12202969) is located downstream of an uncharacterized microRNA gene (MIR2113) and upstream of a transcription factor gene (POU3F2) that has been found to contribute to neocortex development in mice 22 . Using all available proxies for the SNPs with highly to moderately significant evidence for association, we did not find a variant in a gene in LD.…”
Section: Discussionmentioning
confidence: 99%
“…Descending cortical axons first navigate into the VTel around age E13.5, 1 d after TCA emergence into the ventral-most aspects of the VTel (4,9,10). Initially, the corticofugal axon (CFA) and corticothalamic axon (CTA) projections, from cortical layers V and VI, respectively, grow together into the IC, but then diverge.…”
mentioning
confidence: 99%